Multiple Antibiotic Resistance in Planktonic Luminous Bacteria of Indian Penaeid Shrimp Farms (Journal of Scientific Research, 2013)
Prevalence of luminous bacteria (LB) in grow-out pond water and sediment samples, and antibiotic resistance among planktonic LB of two major shrimp farming States of India namely Tamil Nadu and West Bengal were studied. Luminous bacterial counts in the range of log 0.70-3.64/mL pond water and log 2.00-4.90/g pond sediment were recorded. The Tamil Nadu shrimp pond water recorded five planktonic luminous bacterial species, viz. Vibrio fischeri, V. harveyi, V. orientalis, V. splendidus biotype1 and Photobacterium leiognathi; while the West Bengal shrimp pond water had only two species V. harveyi and V. splendidus biotype 1. Vibrio harveyi was the most dominant species in both cases, constituting about 90-97% of the total planktonic LB. Majority of the LB isolates from Tamil Nadu shrimp farms were resistant to ciprofloxacin, gentamycin, nitrofurantoin and oxytetracycline; while the West Bengal strains were resistant to co-trimoxazole and oxytetracycline. None of the 420 planktonic LB was resistant to chloramphenicol. The planktonic V. harveyi recorded minimal inhibitory concentrations ?100 ?g/mL for gentamycin, nitrofurantoin, oxytetracycline and co-trimoxazole. Multiple antibiotic resistance was significantly high (P